A Narrative Review on the Collection and Use of Electronic Patient-Reported Outcomes in Cancer Survivorship Care with Emphasis on Symptom Monitoring - Van Den Hurk, Corina J.G.; Mols, Floortje; Eicher, Manuela; Chan, Raymond J.; Becker, Annemarie; Geleijnse, Gijs; Walraven, Iris; Coolbrandt, Annemarie; Lustberg, Maryam; Velikova, Galina; Charalambous, Andreas; Koczwara, Bogda; et al. (My University, 2022)
Electronic patient-reported outcome (ePRO) applications promise great added value for improving symptom management and health-related quality of life. The aim of this narrative review is to describe the collection and use of ePROs for cancer survivorship care, with an emphasis on ePRO-symptom monitoring. It offers many different perspectives from research settings, while current implementation in routine care is ongoing. ePRO collection optimizes survivorship care by providing insight into the patients' well-being and prioritizing their unmet needs during the whole trajectory from diagnosis to end-of-life. ePRO-symptom monitoring can contribute to timely health risk detection and subsequently allow earlier intervention. Detection is optimized by automatically generated alerts that vary from simple to complex and multilayered. Using ePRO-symptoms during in-hospital consultation enhances the patients' conversation with the health care provider before making informed decisions about treatments, other interventions, or self-management. ePRO(-symptoms) entail specific implementation issues and complementary ethics considerations. The latter is due to privacy concerns, digital divide, and scarcity of adequately representative data for particular groups of patients.
Keywords: Cancer; eHealth; Survivorship; Electronic patient-reported outcomes; Symptoms; Quality of care; Quality of life; Self-management; Ethics